Bouvier et le quatuor cingalais, ou les ambivalences de la « magie » - Jean-Xavier Ridon (Viatica)
The Scorpion-Fish by Nicolas Bouvier is analysed here as an exercise of “white magic”, a term used by Bouvier to describe activities which evoke, like writing, inner energy. The study focuses on the expression of musical structure in travel writing and the way in which Bouvier includes a series of repetitions and echoes, directly modelled on the music of Claude Debussy.